Anthropogenic Effects on Green Infrastructure Spatial Patterns in Kisangani City and Its Urban–Rural Gradient - Julien Bwazani Balandi; Jean-Pierre Pitchou Meniko To Hulu; Kouagou Raoul Sambieni; Yannick Useni Sikuzani; Jean-François Bastin; Charles Mumbere Musavandalo; Timothée Besisa Nguba; Roselande Jesuka; Carlo Sodalo; Léa Mukubu Pika; Jan Bogaert (Land)
Urban and peri-urban expansion significantly influences the spatial pattern of cities and surrounding zones. This study examines the spatial changes in green infrastructure components, specifically focusing on mature forests, short forests, and agricultural and grass lands from 1986 to 2021, using satellite imagery. Two landscape ecology indexes, the percentage of landscape (PLAND), and the largest patch index (LPI), were applied. PLAND provides insights into the proportion of habitat types, capturing overall extent, while LPI elucidates their spatial configuration. The research is conducted in a specific context of increasing urbanization and peri-urbanization in Kisangani city, DR Congo. The findings reveal a decline in both mature and short forests, respectively, from 1986 to 2021, and from 2006 to 2021 alongside a continuous expansion of agricultural and grass lands at the landscape scale. Moreover, the spatial pattern of mature and short forests exhibited significant variations across urban, peri-urban, and rural zones. In the context of 2021, in urban and peri-urban zones, mature forests account for less than 1% of the 2.25 km2 plots, against more than 35% in certain rural plots. Similarly, larger patches of mature forest in urban and peri-urban zones cover less than 0.5% of the 2.25 km2 plots, whereas they exceed 20% in rural zones. From 1986 to 2021, both mature and short forests experienced significant decline and fragmentation, particularly in urban and peri-urban zones, while agricultural and grass lands increased significantly in peri-urban and rural zones. These results raise concerns regarding the functions, services, and opportunities provided by mature and short forests in the context of global change. They also highlight the need for urban planning in Kisangani to prioritize green infrastructure preservation, focusing on maintaining forest connectivity and preventing further fragmentation. Policies should promote sustainable land use in peri-urban zones to achieve a balance between urban expansion and the provision of essential ecosystem services, thereby enhancing long-term resilience.